Comparison of racial distribution of photodermatoses in USA academic dermatology clinics: A multicenter retrospective analysis of 1080 patients over a 10‐year period. Issue 3 (12th March 2020) - Hamel, Remi; Mohammad, Tasneem F.; Chahine, Adam; Joselow, Andrew; Vick, Garrett; Radosta, Stella; Boh, Erin; Alora‐Palli, Maria; Mistur, Rachel L.; Baron, Elma D.; Cooper, Kevin D.; Lim, Henry W.
Abstract: Background: Previous studies at single academic institutions have identified variations in the prevalence of photodermatoses among racial groups. The purpose of the study was to compare the distribution of photodermatoses between Whites and Blacks at four academic medical centers in the USA. Methods: A retrospective chart review was performed at four institutions' general dermatology clinics using diagnoses consistent with the International Classification of Disease (ICD), Ninth and Tenth Revisions, codes related to photodermatoses between August 2006 and August 2016. A total of 9736 charts were manually reviewed and classified. Analyses were performed analyzing the frequency of photodermatoses between Whites and Blacks in the pooled data. Results: There were 1, 080 patients with photodermatoses identified. Statistically significant differences in the frequency of photodermatoses between Whites and Blacks were identified for polymorphous light eruption (more common in Blacks), photoallergic contact dermatitis, phototoxic drug eruption, phytophotodermatitis, porphyria, and solar urticaria (more common in Whites). The most commonly diagnosed photodermatoses were polymorphous light eruption (total 672), and photodermatitis not otherwise specified (total 189). Conclusion: Our study demonstrated significantly higher proportions of polymorphous light eruption in Blacks, and higher proportions of photoallergic contact dermatitis, phototoxic drug eruptions, phytophotodermatitis, porphyrias, and solar urticaria in Whites.